2005
DOI: 10.1590/s0066-782x2005000300004
|View full text |Cite
|
Sign up to set email alerts
|

Estudo comparativo dos resultados da intervenção cirúrgica e da angioplastia na revascularização do miocárdio em portadores de comprometimento multiarterial equivalente

Abstract: In multivessel patients, compared with angioplasty, coronary artery bypass grafting was associated with a lower incidence of long-term events and a reduced need for new interventions (P = 0.001).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…This conclusion is evident in subgroups in which there is proximal involvement of the three main branches, in diabetic patients, when there is myocardial dysfunction and in those patients with injury to the left coronary arterial trunk [8,27]. Studies that compared CABG and PTA in patients with equivalent multiple arterial lesions [28], the event-free survival rate, including acute myocardial infarction, heart-related death and any type of revascularization, always favored surgical revascularization. This study reaffirms a previous study by the same group, MASS-2 [15], in which on comparing both the event-free survival rate and the necessity of new interventions, the outcomes of the Surgical Group were better than the PTA Group and even the results of the Clinical Treatment Group were better than the PTA Group (Figures 1 and 2).…”
mentioning
confidence: 99%
“…This conclusion is evident in subgroups in which there is proximal involvement of the three main branches, in diabetic patients, when there is myocardial dysfunction and in those patients with injury to the left coronary arterial trunk [8,27]. Studies that compared CABG and PTA in patients with equivalent multiple arterial lesions [28], the event-free survival rate, including acute myocardial infarction, heart-related death and any type of revascularization, always favored surgical revascularization. This study reaffirms a previous study by the same group, MASS-2 [15], in which on comparing both the event-free survival rate and the necessity of new interventions, the outcomes of the Surgical Group were better than the PTA Group and even the results of the Clinical Treatment Group were better than the PTA Group (Figures 1 and 2).…”
mentioning
confidence: 99%
“…The improvement in the techniques and instruments allowed such less invasive form of revascularization to be offered to patients with multivessel disease with safety and efficacy similar to those of surgical revascularization reported in several studies. Silva et al 4 have reported the results of a randomized study carried out in a single center in our country, assessing the long-term advantages of both strategies of revascularization regarding the clinical evolution of patients with multivessel coronary disease.…”
mentioning
confidence: 99%